Effectiveness of Using Quizizz Media as an Evaluation of Explanatory Text Learning for Students in Junior High School - Rifa Aulia; Hasnah Faizah; Charlina Charlina (AL-ISHLAH: Jurnal Pendidikan, 2023)
The objective of this study is to assess the efficacy of employing Quizizz as a learning tool in enhancing the engagement and academic performance of eighth-grade students in comprehending explanatory texts. This research used quasi-experimental methodologies, specifically utilising a pre-test and post-test non-equivalent control group design. The study's population consisted of all pupils in the eighth grade. This study employed purposive sampling procedures to choose a total of 44 students from grade seventh in junior high school. The results of the study showed that the use of the Quizizz platform in evaluation activities was in the very good criteria (SB) of 55.91%, and student responses to evaluation activities were in the good category (B) of 44.01%. In the learning outcomes, students showed that the experimental class pretest data got an average of 65.05 and a posttest score of 82.10. In the control class, the pretest results got an average of 62.57, and the posttest results were 76.98. This shows that the average value result of the experimental class is higher than that of the control class. In calculating the hypothesis test sig 0.032 0.05, the hypothesis (H0) was rejected and  (Ha) accepted. Based on the n-gain test results 56.7% which was included in the effective category. It can be concluded that the application of Quizizz media is effective in increasing interest and learning outcomes in evaluation activities for students.